Anaerobic Codigestion of Food Waste and Polylactic Acid: Effect of Pretreatment on Methane Yield and Solid Reduction - Shakira R. Hobbs; Prathap Parameswaran; Barbara Astmann; Jay P. Devkota; Amy E. Landis (Advances in Materials Science and Engineering)
Food waste and biopolymers, plastics derived from plants, are unexploited sources of energy when discarded in landfills without energy recovery. In addition, polylactic acid (PLA) and food waste have complimentary characteristics for anaerobic digestion; both are organic and degrade under anaerobic conditions. Lab-scale reactors were set up to quantify the solubilization of pretreated amorphous and crystalline PLA. Biochemical methane potential (BMP) assays were performed to quantify CH4 production from both treated and untreated PLA in the presence of food waste and anaerobic digested sludge. Amorphous and crystalline PLA reached near-complete solubilization at 97% and 99%, respectively, when alkaline pretreatment was applied. The PLA that received alkaline treatment produced the most of CH4 throughout the run time of 70 days. The PLA without treatment resulted in 54% weight reduction after anaerobic digestion. Results from this study show that alkaline pretreatment has the greatest solid reduction of PLA and maximum production of CH4 when combined with food waste and anaerobic digested sludge.